THE EFFORT TO INCREASE AWARENESS SAFETY AND HEALTH AT SCHOOLS FOR ELEMENTARY SCHOOLS STUDENT USING ROLE PLAY METHOD - Neffrety Nilamsari; Fadilatus Sukma Ika Noviarni; Ratih Damayanti (Darmabakti Cendekia: Journal of Community Service and Engagements, 2019)
Background: Application of Occupational Safety and Health (K3) is not only the scope of the company but also be started from the household and school environment. There are many potential hazards for students at school and can cause an accident or illness for students if not controlled well. Primary school is a form of formal education for children aged 6 to 12 years. Child is curious about a concept. During this period, children have begun to be able to distinguish between good and bad based on their own reasoning. Purpose: The right method was needed to motivated children aged 6-12 years to play safe at the school environment and home. Method: The role play method was used as a tool to stimulate students aged 6-12 years to be able to increase awareness of the importance of applying OSH in the school and home environment especially when playing futsal and bicycles. Result: The understanding scores of playing material was safe during the pre-test with a very good rating of 66.67%, and those who lack understanding 12.90%. An increase in scores after the role play of the criteria was very good up to 69.15% while the lack of understanding criteria can be reduced until 4.25%. Conclusion: The material thas has been given has a positive impact on students awareness. These activities can be improved through children habituation to live safety consciously.